Call for new criteria for monitoring and registering Natura 2000 species data - Meritxell Genovart; Roberto Salguero‐Gomez; Fernando Colchero; Francisco Guil; Joan Rabassa‐Juvanteny; Julia Uriach‐Dasca; Dalia Amor Conde; Jean Michel Gaillard; Tim Coulson (Conservation Biology, 2025)
The European Union's Birds and Habitats Directives are intended to guarantee the persistence of species and natural habitats across member states. To achieve this laudable aim, the Natura 2000 network of protected areas was established in 1992. Since then, member states are required to regularly monitor species and habitats and report findings to the European Commission, which requires substantial investment from all countries. The Natura 2000 network is an invaluable example of a large‐scale coordinated network developed to address major conservation issues. Based on our analysis of the 2020 Species Natura 2000 database and on expert opinions by Natura 2000 executives, we found that the network is failing to adequately show biodiversity status and guide conservation because it does not allow cross‐border comparisons of species’ and populations’ conservation status. The main contributing factor to this failure is that member states frequently fail to follow reporting EU guidelines, resulting in heterogeneity in criteria for monitoring and registering species among Natura 2000 areas. We advocate developing new unified and realistic criteria for monitoring and reporting species data that correctly allow cross‐border comparisons and conservation diagnosis. We propose that monitoring protocols and current criteria be modified slightly by considering species’ life‐history strategies, distribution, and conservation status. We do not suggest a major overhaul of the directives; rather, we propose debate on how relatively small changes in guidelines could improve the utility of the huge amount of data collected from the Natura 2000 network.

Density Dependence Shapes Life‐History Trade‐Offs in a Food‐Limited Population - Harman Jaggi; Wenyun Zuo; Rosemarie Kentie; Jean‐Michel Gaillard; Tim Coulson; Shripad Tuljapurkar (Ecology Letters, 2024)
Quantifying trade‐offs within populations is important in life‐history theory. However, most studies focusing on life‐history trade‐offs focus on two traits and assume trade‐offs to be static. Our work provides a framework for understanding covariation among multiple traits and how population density influences the traits. Using detailed individual‐based data for Soay sheep, we find density strongly shapes life‐history trade‐offs and distribution of lifetime reproductive success (LRS). At low density, a trade‐off between juvenile survival and growth structures life‐history variation, whereas at equilibrium density, trade‐off between reproduction and juvenile survival is the major structuring axes. Contrary to Lomnicki's prediction, we find that at high density, there is little variation in the LRS over the sizes (large juveniles and adults) that contribute to reproduction. Our results advance an understanding of dynamic nature of trade‐offs offer insights into how high‐density limits diversity of individual life histories and have implications for evolution via density‐dependent selection.

Celebrating wildlife population recovery through education - Gioele Passoni; Tim Coulson; Francesca Cagnacci (Trends in Ecology & Evolution, 2024)

The effect of divergent and parallel selection on the genomic landscape of divergence - Hisham A. A. Ali; Tim Coulson; Sonya M. Clegg; Claudio S. Quilodrán (Molecular Ecology, 2024)
While the role of selection in divergence along the speciation continuum is theoretically well understood, defining specific signatures of selection in the genomic landscape of divergence is empirically challenging. Modelling approaches can provide insight into the potential role of selection on the emergence of a heterogenous genomic landscape of divergence. Here, we extend and apply an individual‐based approach that simulates the phenotypic and genotypic distributions of two populations under a variety of selection regimes, genotype–phenotype maps, modes of migration, and genotype‐environment interactions. We show that genomic islands of high differentiation and genomic valleys of similarity may respectively form under divergent and parallel selection between populations. For both types of between‐population selection, negative and positive frequency‐dependent selection within populations generated genomic islands of higher magnitude and genomic valleys of similarity, respectively. Divergence rates decreased under strong dominance with divergent selection, as well as in models including genotype‐environment interactions under parallel selection. For both divergent and parallel selection models, divergence rate was higher under an intermittent migration regime between populations, in contrast to a constant level of migration across generations, despite an equal number of total migrants. We highlight that interpreting a particular evolutionary history from an observed genomic pattern must be done cautiously, as similar patterns may be obtained from different combinations of evolutionary processes. Modelling approaches such as ours provide an opportunity to narrow the potential routes that generate the genomic patterns of specific evolutionary histories.

Investigating tritrophic interactions using bioenergetic demographic models - Gioele Passoni; Tim Coulson; Francesca Cagnacci; Peter Hudson; Daniel R. Stahler; Douglas W. Smith; Shelly Lachish (Ecology, 2024)
A central debate in ecology has been the long‐running discussion on the role of apex predators in affecting the abundance and dynamics of their prey. In terrestrial systems, research has primarily relied on correlational approaches, due to the challenge of implementing robust experiments with replication and appropriate controls. A consequence of this is that we largely suffer from a lack of mechanistic understanding of the population dynamics of interacting species, which can be surprisingly complex. Mechanistic models offer an opportunity to examine the causes and consequences of some of this complexity. We present a bioenergetic mechanistic model of a tritrophic system where the primary vegetation resource follows a seasonal growth function, and the herbivore and carnivore species are modeled using two integral projection models (IPMs) with body mass as the phenotypic trait. Within each IPM, the demographic functions are structured according to bioenergetic principles, describing how animals acquire and transform resources into body mass, energy reserves, and breeding potential. We parameterize this model to reproduce the population dynamics of grass, elk, and wolves in northern Yellowstone National Park (USA) and investigate the impact of wolf reintroduction on the system. Our model generated predictions that closely matched the observed population sizes of elk and wolf in Yellowstone prior to and following wolf reintroduction. The introduction of wolves into our basal grass–elk bioenergetic model resulted in a population of 99 wolves and a reduction in elk numbers by 61% (from 14,948 to 5823) at equilibrium. In turn, vegetation biomass increased by approximately 25% in the growing season and more than threefold in the nongrowing season. The addition of wolves to the model caused the elk population to switch from being food‐limited to being predator‐limited and had a stabilizing effect on elk numbers across different years. Wolf predation also led to a shift in the phenotypic composition of the elk population via a small increase in elk average body mass. Our model represents a novel approach to the study of predator–prey interactions, and demonstrates that explicitly considering and linking bioenergetics, population demography and body mass phenotypes can provide novel insights into the mechanisms behind complex ecosystem processes.

Climate change is predicted to cause population collapse in a cooperative breeder - Daniella Rabaiotti; Tim Coulson; Rosie Woodroffe (Global Change Biology, 2023)
It has been suggested that animals may have evolved cooperative breeding strategies in response to extreme climatic conditions. Climate change, however, may push species beyond their ability to cope with extreme climates, and reduce the group sizes in cooperatively breeding species to a point where populations are no longer viable. Predicting the impact of future climates on these species is challenging as modelling the impact of climate change on their population dynamics requires information on both group‐ and individual‐level responses to climatic conditions. Using a single‐sex individual‐based model incorporating demographic responses to ambient temperature in an endangered species, the African wild dog Lycaon pictus , we show that there is a threshold temperature above which populations of the species are predicted to collapse. For simulated populations with carrying capacities equivalent to the median size of real‐world populations (nine packs), extinction risk increases once temperatures exceed those predicted in the best‐case climate warming scenario (Representative Concentration Pathway [RCP] 2.6). The threshold is higher (between RCP 4.5 and RCP 6.0) for larger simulated populations (30 packs), but 84% of real‐world populations number

Going with the flow: The case of three tropical reef fish transported to cool temperate waters following an extreme marine heatwave - Peter G. Coulson; Tim Leary; Arani Chandrapavan; Corey B. Wakefield; Stephen J. Newman (Regional Studies in Marine Science, 2023)

Reproductive dispersion and damping time scale with life‐history speed - Sha Jiang; Harman Jaggi; Wenyun Zuo; Madan K. Oli; Tim Coulson; Jean‐Michel Gaillard; Shripad Tuljapurkar (Ecology Letters, 2022)
Iteroparous species may reproduce at many different ages, resulting in a reproductive dispersion that affects the damping of population perturbations, and varies among life histories. Since generation time () is known to capture aspects of life‐history variation, such as life‐history speed, does also determine reproductive dispersion () or damping time ()? Using phylogenetically corrected analyses on 633 species of animals and plants, we find, firstly, that reproductive dispersion scales isometrically with . Secondly, and unexpectedly, we find that the damping time () does not scale isometrically with generation time, but instead changes only as with (also, there is a similar scaling with ). This non‐isometric scaling implies a novel demographic contrast: increasing generation times correspond to a proportional increase in reproductive dispersion, but only to a slower increase in the damping time. Thus, damping times are partly decoupled from the slow‐fast continuum, and are determined by factors other than allometric constraints.

Distributions of LRS in varying environments - Shripad Tuljapurkar; Wenyun Zuo; Tim Coulson; Carol Horvitz; Jean‐Michel Gaillard (Ecology Letters, 2021)
The lifetime reproductive success (LRS) of individuals is affected by random events such as death, realized growth or realized reproduction, and the outcomes of these events can differ even when individuals have identical probabilities. Another source of randomness arises when these probabilities also change over time in variable environments. For structured populations in stochastic environments, we extend our recent method to determine how birth environment and birth stage determine the random distribution of the LRS. Our results provide a null model that quantifies effects on LRS of just the birth size or stage. Using Roe deer Capreolus capreolus as a case study, we show that the effect of an individual's birth environment on LRS varies with the frequency of environments and their temporal autocorrelation, and that lifetime performance is affected by changes in the pattern of environmental states expected as a result of climate change.

Towards a more precise – and accurate – view of eco‐evolution - Ronald D. Bassar; Tim Coulson; Joseph Travis; David N. Reznick (Ecology Letters, 2021)
Over the past 15 years, the number of papers focused on ‘eco‐evo dynamics’ has increased exponentially (Figure 1 ). This pattern suggests the rapid growth of a new, integrative discipline. We argue this overstates the case. First, the terms ‘eco‐evo dynamics’ and ‘eco‐evo interactions’ are used too imprecisely. As a result, many studies that claim to describe eco‐evo dynamics are actually describing basic ecological or evolutionary processes. Second, these terms are often used as if the study of how ecological and evolutionary processes are intertwined is novel when, in fact, it is not. The result is confusion over what the term ‘eco‐evolution’ and its derivatives describe. We advocate a more precise definition of eco‐evolution that is more useful in efforts to understand and characterise the diversity of ecological and evolutionary processes and that focuses attention on the subset of those processes that occur only when ecological and evolutionary timescales are comparable. Number of papers returned, by year, by a search in Web of Science with the term ‘eco‐evolutionary dynamics' as accessed on 7 January 2021. image

Can we use a functional trait to construct a generalized model for ungulate populations? - Lochran W. Traill; Floriane Plard; Jean‐Michel Gaillard; Tim Coulson (Ecology, 2021)
Ecologists have long desired predictive models that allow inference on population dynamics, where detailed demographic data are unavailable. Integral projection models (IPMs) allow both demographic and phenotypic outcomes at the level of the population to be predicted from the distribution of a functional trait, like body mass. In species where body mass markedly influences demographic rates, as is the rule among mammals, then IPMs provide not only opportunity to assess the population responses to a given environment, but also improve our understanding of the complex interplay between traits and demographic outcomes. Here, we develop a body‐mass‐based approach to constructing generalized, predictive IPMs for species of ungulates covering a broad range of body size (25–400 kg). Despite our best efforts, we found that a reliable and general, functional, trait‐based model for ungulates was unattainable even after accounting for among‐species variation in both age at first reproduction and litter size. We attribute this to the diversity of reproductive tactics among similar‐sized species of ungulates, and to the interplay between density‐dependent and environmental factors that shape demographic parameters independent of mass at the local scale. These processes thus drive population dynamics and cannot be ignored. Environmental context generally matters in population ecology, and our study shows this may be the case for functional traits in vertebrate populations.

We live in a changing world, but that shouldn’t mean we abandon the concept of equilibrium - Tim Coulson (Ecology Letters, 2021)
Ecological systems are no longer at equilibrium, but over much of the history of the Earth, the natural world has been in stationary states, that are punctuated by periods of transience. Just because we have knocked our planet away from a stable state, doesn't mean we have to abandon the concept of equilibrium when we strive to understand the dynamics of the natural world.

Phenological asynchrony: a ticking time‐bomb for seemingly stable populations? - Emily G. Simmonds; Ella F. Cole; Ben C. Sheldon; Tim Coulson (Ecology Letters, 2020)
Climate change has been shown to induce shifts in the timing of life‐history events. As a result, interactions between species can become disrupted, with potentially detrimental effects. Predicting these consequences has proven challenging. We apply structured population models to a well‐characterised great tit‐caterpillar model system and identify thresholds of temporal asynchrony, beyond which the predator population will rapidly go extinct. Our model suggests that phenotypic plasticity in predator breeding timing initially maintains temporal synchrony in the face of environmental change. However, under projections of climate change, predator plasticity was insufficient to keep pace with prey phenology. Directional evolution then accelerated, but could not prevent mismatch. Once predator phenology lagged behind prey by more than 24 days, rapid extinction was inevitable, despite previously stable population dynamics. Our projections suggest that current population stability could be masking a route to population collapse, if high greenhouse gas emissions continue.

Life‐history strategy varies with the strength of competition in a food‐limited ungulate population - Rosemarie Kentie; Sonya M. Clegg; Shripad Tuljapurkar; Jean‐Michel Gaillard; Tim Coulson (Ecology Letters, 2020)
Fluctuating population density in stochastic environments can contribute to maintain life‐history variation within populations via density‐dependent selection. We used individual‐based data from a population of Soay sheep to examine variation in life‐history strategies at high and low population density. We incorporated life‐history trade‐offs among survival, reproduction and body mass growth into structured population models and found support for the prediction that different life‐history strategies are optimal at low and high population densities. Shorter generation times and lower asymptotic body mass were selected for in high‐density environments even though heavier individuals had higher probabilities to survive and reproduce. In contrast, greater asymptotic body mass and longer generation times were optimal at low population density. If populations fluctuate between high density when resources are scarce, and low densities when they are abundant, the variation in density will generate fluctuating selection for different life‐history strategies, that could act to maintain life‐history variation.

Skewed distributions of lifetime reproductive success: beyond mean and variance - Shripad Tuljapurkar; Wenyun Zuo; Tim Coulson; Carol Horvitz; Jean‐Michel Gaillard (Ecology Letters, 2020)
Lifetime reproductive performance is quantified here by the LRS (lifetime reproductive success), the random number of offspring an individual produces over its lifetime. Many field studies find that distributions of LRS among individuals are non‐normal, zero‐inflated and highly skewed. These results beg the question, what is the distribution of LRS predicted by demographic models when the only source of randomness is demographic stochasticity? Here we present the first exact analysis of the probability distribution of LRS for species described by age + stage models; our analysis starts with estimated vital rates. We illustrate with three examples: the Hadza, human hunter‐foragers (age‐only), the evergreen tree Tsuga canadensis (stage‐only) and Roe deer, Capreolus capreolus (age + stage). For each we obtain the exact distribution of LRS, but also calculate and discuss the first three moments. Our results point to important questions about how such LRS distributions affect natural selection, and life history evolution.

Size and density mediate transitions between competition and facilitation - Hayley Cameron; Tim Coulson; Dustin J. Marshall (Ecology Letters, 2019)
Species simultaneously compete with and facilitate one another. Size can mediate transitions along this competition–facilitation continuum, but the consequences for demography are unclear. We orthogonally manipulated the size of a focal species, and the size and density of a heterospecific neighbour, in the field using a model marine system. We then parameterised a size‐structured population model with our experimental data. We found that heterospecific size and density interactively altered the population dynamics of the focal species. Size determined whether heterospecifics facilitated (when small) or competed with (when large) the focal species, while density strengthened these interactions. Such size‐mediated interactions also altered the pace of the focal’s life history. We provide the first demonstration that size and density mediate competition and facilitation from a population dynamical perspective. We suspect such effects are ubiquitous, but currently underappreciated. We reiterate classic cautions against inferences about competitive hierarchies made in the absence of size‐specific data.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Warming springs and habitat alteration interact to impact timing of breeding and population dynamics in a migratory bird - Rosemarie Kentie; Tim Coulson; Jos C. E. W. Hooijmeijer; Ruth A. Howison; A. H. Jelle Loonstra; Mo A. Verhoeven; Christiaan Both; Theunis Piersma (Global Change Biology, 2018)
In seasonal environments, increasing spring temperatures lead many taxa to advance the timing of reproduction. Species that do not may suffer lower fitness. We investigated why black‐tailed godwits ( Limosa limosa limosa ), a ground‐breeding agricultural grassland shorebird, have not advanced timing of reproduction during the last three decades in the face of climate change and human‐induced habitat degradation. We used data from an 11‐year field study to parameterize an Integral Projection Model to predict how spring temperature and habitat quality simultaneously influence the timing of reproduction and population dynamics. We found apparent selection for earlier laying, but not a correlation between the laying dates of parents and their offspring. Nevertheless, in warmer springs, laying dates of adults show a stronger positive correlation with laying date in previous springs than in cooler ones, and this leads us to predict a slight advance in the timing of reproduction if spring temperatures continue to increase. We also show that only in landscapes with low agricultural activity, the population can continue to act as a source. This study shows how climate change and declining habitat quality may enhance extinction risk.

New innovations for 2018 and beyond - Tim Coulson; Peter Thrall; Jon Chase; Helmut Hillebrand; Vanessa Ezenwa; John Drake; Nathalie Espuno; Stephane Hello (Ecology Letters, 2018)

Predicting coexistence in species with continuous ontogenetic niche shifts and competitive asymmetry - Ronald D. Bassar; Joseph Travis; Tim Coulson (Ecology, 2017)
A longstanding problem in ecology is whether structured life cycles impede or facilitate coexistence between species. Theory based on populations with only two discrete stages in the life‐cycle indicates that for two species to coexist, at least one must shift its niche between stages and each species must be a better competitor in one of the niches. However, in many cases, niche shifts are associated with changes in an underlying continuous trait like body size and we have few predictions concerning conditions for coexistence for such a widespread form of ontogenetic development. We develop a framework for analyzing species coexistence based on Integral Projection Models ( IPM s) that incorporates continuous ontogenetic changes in both the resource niche and competitive ability. We parameterize the model using experimental data from Trinidadian guppies and show how niche shifts and competitive symmetries impact species coexistence. Overall, our results show that the effects of competition on fitness depend upon trait‐mediated niche‐separation, trait‐mediated competitive asymmetry in the part of the niche that is shared across body sizes, and the sensitivity of fitness to body size. Interactions among these processes generate multiple routes to coexistence. We discuss how our modeling framework expands results from two‐stage models to mutli‐stage or continuous stage models and allows for deriving predictions that can be tested in populations displaying continuous changes in niche use and competitive ability.

The effects of asymmetric competition on the life history of Trinidadian guppies - Ronald D. Bassar; Dylan Z. Childs; Mark Rees; Shripad Tuljapurkar; David N. Reznick; Tim Coulson (Ecology Letters, 2016)
The effects of asymmetric interactions on population dynamics has been widely investigated, but there has been little work aimed at understanding how life history parameters like generation time, life expectancy and the variance in lifetime reproductive success are impacted by different types of competition. We develop a new framework for incorporating trait‐mediated density‐dependence into size‐structured models and use Trinidadian guppies to show how different types of competitive interactions impact life history parameters. Our results show the degree of symmetry in competitive interactions can have dramatic effects on the speed of the life history. For some vital rates, shifting the competitive superiority from small to large individuals resulted in a doubling of the generation time. Such large influences of competitive symmetry on the timescale of demographic processes, and hence evolution, highlights the interwoven nature of ecological and evolutionary processes and the importance of density‐dependence in understanding eco‐evolutionary dynamics.

Editorial - Tim Coulson (Ecology Letters, 2016)

The indirect effects of habitat disturbance on the bird communities in a tropical African forest - Christos Mammides; Matthias Schleuning; Katrin Böhning-Gaese; Gertrud Schaab; Nina Farwig; Costas Kadis; Tim Coulson (Biodiversity and Conservation, 2015)

Using simulations of past and present elephant (Loxodonta africana) population numbers in the Okavango Delta Panhandle, Botswana to improve future population estimates - Anna Songhurst; Michael Chase; Tim Coulson (Wetlands Ecology and Management, 2015)

The influence of birth date via body mass on individual fitness in a long‐lived mammal - Floriane Plard; Jean-Michel Gaillard; Tim Coulson; A. J. Mark Hewison; Mathieu Douhard; François Klein; Daniel Delorme; Claude Warnant; Christophe Bonenfant (Ecology, 2015)
The timing of birth has marked impacts on early life and early development of newborns in many species. In seasonal environments, early‐born offspring often survive and grow better than late‐born offspring, but despite the long‐lasting effects of early conditions on life history traits, the influence of birth date on fitness has rarely been investigated for long‐lived species. In this study, we analyzed both the short‐ and long‐term effects of birth date on individual life history traits and explored its subsequent impact on individual fitness in a population of roe deer. We considered both the direct effects, as well as the indirect effects of birth date mediated through the effects of body mass, on demographic parameters. We found that in addition to short‐term effects on early body growth and survival, birth date generates “silver spoon” effects on adult life history traits of female roe deer. Birth date had long‐lasting effects on female adult body mass such that early‐born females were, on average, 3 kg heavier as adults than late‐born females, although female adult survival was similar between these categories. Based on the observed relationships between birth date, body mass, and demographic parameters, we built an integral projection model describing the simultaneous distributions of birth date and body mass to quantify the fitness consequences of birth date. We found that the fitness of early‐born females was higher than that of late‐born females. These long‐lasting effects of birth date on fitness were mostly mediated through the influence of birth date on recruitment and adult body mass. By determining development of newborns during the early stages of life, birth date has a critical influence on each step of an individual's subsequent life history trajectory.

Will central Wyoming elk stop migrating to Yellowstone, and should we care? - Jack Massey; Sarah Cubaynes; Tim Coulson (Ecology, 2013)

A comparative analysis of the factors promoting deer invasion - Richard Fautley; Tim Coulson; Vincent Savolainen (Biological Invasions, 2012)

Predation, individual variability and vertebrate population dynamics - Nathalie Pettorelli; Tim Coulson; Sarah M. Durant; Jean-Michel Gaillard (Oecologia, 2011)

Behavioural switching in a central place forager: patterns of diving behaviour in the macaroni penguin (Eudyptes chrysolophus) - Tom Hart; Richard Mann; Tim Coulson; Nathalie Pettorelli; Phil Trathan (Marine Biology, 2010)

Mortality in adult intensive care patients with severe systemic inflammatory response syndromes is strongly associated with the hypo-immune TNF −238A polymorphism - John V. Pappachan; Tim G. Coulson; Nicholas J. A. Child; David J. Markham; Sarah M. Nour; Mark C. K. Pulletz; Matthew J. Rose-Zerilli; Kim de Courcey-Golder; Sheila J. Barton; Ian A. Yang; John W. Holloway (Immunogenetics, 2009)

Estimating stochastic elasticities directly from longitudinal data - C. V. Haridas; Shripad Tuljapurkar; Tim Coulson (Ecology Letters, 2009)
The elasticities of long‐run population growth rate with respect to vital rates are useful in studying selection on vital rates, and in evaluating management policy that aims to control vital rates. In temporally varying environments, elasticity is often calculated from simulations that assume a probability distribution for the environmental states. Here we develop a method to estimate elasticities directly from demographic data. Using a time‐series of demographic matrices and age‐structure we construct a consistent statistical estimator of elasticity that converges to the correct limiting value as the sample length increases. We also construct confidence intervals for elasticities from temporal data and suggest tools for testing hypotheses about the strength of selection. We use data on a natural population to show that our method can indeed accurately estimate elasticities using relatively short time series.

Heterozygosity–fitness correlations and associative overdominance: new detection method and proof of principle in the Iberian wild boar - AURELIO F. MALO; TIM COULSON (Molecular Ecology, 2009)
Heterozygosity‐fitness correlations (HFC) may result from a genome‐wide process — inbreeding — or local effects within the genome. The majority of empirical studies reporting HFCs have attributed correlations to inbreeding depression. However, HFCs are unlikely to be caused by inbreeding depression because heterozygosity measured at a small number of neutral markers is unlikely to accurately capture a genome‐wide pattern. Testing the strengths of localized effects caused by associative overdominance has proven challenging. In their current paper, Amos and Acevedo‐Whitehouse present a novel test for local HFCs. Using stochastic simulations, they determine the conditions under which single‐locus HFCs arise, before testing the strength of the correlation between the neutral marker and a linked gene under selection in their simulations. They used insights gained from simulation to statistically investigate the likely cause of correlations between heterozygosity and disease status using data on bovine tuberculosis infections in a wild boar population. They discover that a single microsatellite marker is an excellent predictor of tuberculosis progression in infected individuals. The results are relevant for wild boar management but, more generally, they demonstrate how single‐locus HFCs could be used to identify coding loci under selection in free‐living populations.

Are local weather, NDVI and NAO consistent determinants of red deer weight across three contrasting European countries? - MARÍA MARTÍNEZ‐JAUREGUI; ALFONSO SAN MIGUEL‐AYANZ; ATLE MYSTERUD; CARLOS RODRÍGUEZ‐VIGAL; TIM CLUTTON‐BROCK; ROLF LANGVATN; TIM COULSON (Global Change Biology, 2009)
There are multiple paths via which environmental variation can impact herbivore ecology and this makes the identification of drivers challenging. Researchers have used diverse approaches to describe the association between environmental variation and ecology, including local weather, large‐scale patterns of climate, and satellite imagery reflecting plant productivity and phenology. However, it is unclear to what extent it is possible to find a single measure that captures climatic effects over broad spatial scales. There may, in fact, be no a priori reason to expect populations of the same species living in different areas to respond in the same way to climate as their population may experience limiting factors at different times of the year, and the forms of regulation may differ among populations. Here, we examine whether the same environmental indices [seasonal Real Bioclimatic Index (RBI), seasonal Normalized Difference Vegetation Index (NDVI) and winter North Atlantic Oscillation (NAO)] influence body size in different populations of a large ungulate living in Mediterranean Spain, Western Scotland and Norway. We found substantial differences in the pattern of weight change over time in adult female red deer among study areas as well as different environmental drivers associated with variation in weight. The lack of general patterns for a given species at a continental scale suggest that detailed knowledge regarding the way climate affects local populations is often necessary to successfully predict climate impact. We caution against extrapolation of results from localized climate–population studies to broad spatial scales.

CROSS‐GENERATIONAL EFFECTS OF HABITAT AND DENSITY ON LIFE HISTORY IN RED DEER - Philip D. McLoughlin; Tim Coulson; Tim Clutton-Brock (Ecology, 2008)
We used long‐term data on movements, survival, and reproduction of female red deer ( Cervus elaphus Linnaeus) of the Isle of Rum, Scotland (1970–2001), to explain variation in life history (age at maturity) from a hind's access to habitat resources and exposure to local density, and cross‐generational (maternal) effects on observed relationships. We described each hind's use of resources relative to availability in the study area from an individual‐based resource selection function (RSF); we defined local density as the total number of hinds aged ≥1 year within the subpopulation cluster to which an individual belonged. The likelihood of a hind producing her first calf in the period from birth to the end of the summer in which she turned age 3 was positively related to relative use of Agrostis / Festuca grasslands and other low‐elevation communities, and inversely related to a hind's mean annual local density. However, when we considered both a daughter's RSF and exposure to local density and her mother's RSF and exposure to local density, maternal data alone most parsimoniously explained variation in age at maturity of daughters. Mothers were able to lower age at maturity in their daughters in two, non‐mutually exclusive ways. First, birth mass of daughters was inversely related to age at maturity, and mothers that used relatively less uplands ( Calluna ‐dominated heath and heather moorland) and occupied areas of lower density produced larger offspring. Second, mothers could establish a home range that enabled daughters to mature in areas with access to high quality Agrostis / Festuca grasslands at low density. Lifetime reproductive success was inversely associated with a hind's age at maturity via extension of the reproductive life span. Longevity did not change in association with age at maturity. Patterns in how animals use available habitat resources may depend on that of previous generations, especially at larger scales of resource selection.

THE DEMOGRAPHIC CONSEQUENCES OF THE COST OF REPRODUCTION IN UNGULATES - Gil Proaktor; Tim Coulson; E. J. Milner-Gulland (Ecology, 2008)
The cost of reproduction can generate covariation between demographic rates that can potentially influence demography and population dynamics in long‐lived iteroparous species. However, there has been relatively little work linking the survival cost of reproduction and population dynamics. The apparent scarcity of information on this important link is potentially due to covariation between vital rates, which can substantially influence fluctuations in population size. In this paper we examine the opportunity for survival costs of reproduction to leave a dynamic signature using a simulation model based broadly on an ungulate life history. We find that an increase in the cost delays the onset of reproduction and reduces reproductive rates of young, but not of prime‐age, females. Accordingly, the number of offspring produced declines and the interval between reproductive events increases among young females experiencing high cost. These effects are translated to an age structure skewed toward young ages and reduced population density. These results suggest that, by delaying reproduction when conditions deteriorate, females protect their survival during the critical first three years of life, after which the negative effect of reproduction on survival declines. Unless conditions for reproduction are severe, it is not profitable to delay reproduction beyond age 3 years due to the high risk of death before having a chance to reproduce. We also demonstrate that lack of adjustment of reproductive strategies to elevated levels of the cost of reproduction, for example due to rapid changes in environmental conditions, results in lower average density and longevity compared to females that have sufficient time to adjust to changes in the cost. This suggests that even moderate costs of reproduction may have a major negative effect on population dynamics of ungulates.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

A latitudinal gradient in climate effects on seabird demography: results from interspecific analyses - HANNO SANDVIK; TIM COULSON; BERNT‐ERIK SÆTHER (Global Change Biology, 2008)
For an understanding of the effect of climate change on animal population dynamics, it is crucial to be able to identify which climatologic parameters affect which demographic rate, and what the underlying mechanistic links are. An important reason for why the interactions between demography and climate still are poorly understood is that the effects of climate vary both geographically and taxonomically. Here, we analyse interspecifically how different climate variables affect the breeding success of North Atlantic seabird species along latitudinal and longitudinal gradients. By approaching the problem comparatively, we are able to generalize across populations and species. We find a strong interactive effect of climate and latitude on breeding success. Of the climatic variables considered, local sea surface temperatures during the breeding season tend to be more relevant than the North Atlantic Oscillation (NAO). However, the effect of NAO on breeding success shows a clear geographic pattern, changing in sign from positive in the south to negative in the north. If this interaction is taken account of, the model explains more variation than any model with sea surface temperature. This superiority of the NAO index is due to its ability to capture effects of more than one season in a single parameter. Mechanistically, however, several lines of evidence suggest that sea surface temperature is the biologically most relevant explanatory variable.

Sex-ratio variation in Soay sheep - Jan Lindström; Tim Coulson; Loeske Kruuk; Mads Forchhammer; Dave Coltman; Tim Clutton-Brock (Behavioral Ecology and Sociobiology, 2002)

The Science of Overabundance: Deer Ecology and Population Management - Tim Coulson (Biodiversity and Conservation, 1999)